Researching the military - Carreiras, Helena; Castro, Celso 1963-; Frederic, Sabina (Cass military studies, 2016)
Researching the Military focuses on the experiences of researchers who study the military around the world. It explores the historical, social, institutional and personal factors that frame research and scrutinize the way knowledge in this area impacts society and policy. More than merely analyzing research experiences (yet necessarily including them), it is also about the experiences of researchers, their position with regard to the object of their studies, the institutional context where they work and the way their research impacts the academic and policy-making fields in the respective countries. The common theme to the various chapters is reflexivity, a conscious effort at addressing the conditions of research and the position of the researcher and the research participants in that interface. By collecting diverse experiences of researchers from across the world, this volume aims to enhance reflexivity in the field of military studies and to encourage the exchange of knowledge between the academic field and the military arena. This book will be of much interest to students of military studies, research methods, sociology, social anthropology and security studies, in general.